2015
DOI: 10.14737/journal.aavs/2016.4.1.25.34
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pesticide Residues in Edible and Unhatched Chicken Eggs in Sharkia Province, Egypt

Abstract: | This work is proposed to investigate pesticide residues in chicken eggs in El-Sharkia Province, Egypt. Analysis of pesticide residues was performed on 120 egg samples included 80 random edible egg samples (40 farm and 40 home produced hen eggs) and other 40 unhatched eggs. Edible eggs were collected from different stores, places and supermarkets. unhatched incubated eggs were collected from different hatcheries during the winter season. Organochlorine pesticides (OCPs) and organophophorous insecticides (OPIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…A study conducted in Jordan on 134 egg samples analyzed for OCP residues showed that 28% (38 samples) of the examined eggs were contaminated with OCP residues with a high level of HCHs and DDTs (Ahmad et al., ). A study in Egypt detected aldrin in 25% of farm or home‐grown eggs (Abdelfatah & Abu‐Zeid, ), which is lower than our finding (34%). Study in Spain showed that examined egg samples were free from any traces (Luzardo et al., ) whereas a report from Belgium showed that aldrin was present in only 3% to 5% of the samples above the acceptable limit, although its uses was banned for more than 25 years (Windal et al., ).…”
Section: Discussioncontrasting
confidence: 99%
“…A study conducted in Jordan on 134 egg samples analyzed for OCP residues showed that 28% (38 samples) of the examined eggs were contaminated with OCP residues with a high level of HCHs and DDTs (Ahmad et al., ). A study in Egypt detected aldrin in 25% of farm or home‐grown eggs (Abdelfatah & Abu‐Zeid, ), which is lower than our finding (34%). Study in Spain showed that examined egg samples were free from any traces (Luzardo et al., ) whereas a report from Belgium showed that aldrin was present in only 3% to 5% of the samples above the acceptable limit, although its uses was banned for more than 25 years (Windal et al., ).…”
Section: Discussioncontrasting
confidence: 99%
“…A review of the MRLs for DMT in poultry tissues and eggs according to European regulations (European Food Safety Authority, 2015) showed that 20 μg/kg was the MRL for poultry muscle, liver and eggs, while poultry fat was 100 μg/kg. Abdelfatah and Abu-Zeid (2015) showed that DMT residues were detected in 25% of farm-produced eggs.…”
Section: Residues Of Dmt In the Eggs Skin And Musclementioning
confidence: 99%
“…Deltamethrin (DMT) (one of the pyrethroids) has become an insecticide of choice in many countries owing to its low toxicity (Elias, 2013), while a number of new publications confirmed its toxicity in humans and birds (Chandra et al, 2013). A determination of DMT residues in eggs and meat was studied by Abdelfatah and Abu-Zeid (2015).…”
Section: Introductionmentioning
confidence: 99%